Application of Restorative Justice in Cases of Domestic and Child Violence - Fatin Hamamah (Journal of Law and Humanity Studies, 2024)
Restorative justice (RJ) is an alternative approach to resolving criminal cases that focuses on victim recovery, perpetrator rehabilitation, and community reintegration. In the context of domestic and child violence, this approach offers the potential for a more inclusive and sustainable resolution compared to traditional retributive approaches. However, there is debate about the effectiveness of RJ in cases of violence that have profound psychological and physical impacts on victims. The issue at hand is whether RJ can provide adequate justice without reducing legal protection for victims. This study offers novelty by examining the application of RJ in cases of domestic and child violence in Indonesia, where RJ laws and policies are still developing. The purpose of the study is to identify the challenges and opportunities for implementing RJ in these cases and to evaluate the extent to which this approach is able to create restorative justice for victims and perpetrators. This study uses a qualitative method with case studies on several cases of domestic and child violence resolved through RJ in various regions. The findings indicate that RJ can be effective in facilitating victim recovery, but its implementation requires a strong support structure, including professional counselors and clear legal protection. The conclusion of this study confirms that RJ has great potential in resolving domestic violence cases, but its implementation must be carried out carefully to ensure justice and protection for victims. The implication is that this study encourages policy makers to design a more comprehensive and inclusive RJ framework in handling domestic violence.